IMPLEMENTASI SUPERVISI AKADEMIK KEPALA SEKOLAH MIN TERNATE DI DESA PULAU BUAYA, KECAMATAN ALOR BARAT LAUT, KABUPATEN ALOR, NUSA TENGGARA TIMUR - Yakin Akbar Asikin (Universitas Muhammadiyah Ponorogo, 2018)
The research was done in order to find out: 1) Planning academic supervision of the headmaster of MIN Ternate ; 2) Implementation academic supervision of the headmaster of MIN ternate; 3) The assessment and following up of academic supervision of the headmaster of MIN Ternate. The approach, which was used in the research, was descriptive cualitative. Data was taken by observation, interview, and documents of school. And the source data was from the headmaster of Madrasah, vice principals, homeroom teachers, and teachers. Data analysis of the research used reduction, presentation, and verification. The result of the research has showed that the headmaster of MIN Ternate built strategy in planning academic supervision, strategy was built then the force would be formed. Building strategy in planning academic supervision through coaching program, implementation program. The implementation of academic supervision as the implementation from duty and function as a supervisor in the dimension of supervision with personal approach and program in order to build teacher’s spirit in teaching. The strategy that was built in the implementation of academic supervision was started by checking learning administration, used visiting class technique, class observation, observation in learning process, personal and group conversations. The assessment of academic supervision as an implementation of supervisor function in the assessment dimension. The strategy of the headmaster to follow up the result of academic supervision in order to improve and develop teacher’s ability in teaching through direct and indirect coaching such as: gave warning or doing curriculum accompaniment activity.